Wsparcie społeczne dla osób z niepełnosprawnością a refleksja nad „dobrą” i „złą” charytatywnością - Podgórska-Jachnik, Dorota (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Difference/disability is associated with limitations in social contacts and the risk of social exclusion. Charity and philanthropy not only are an opportunity for people with disabilities but also pose a threat. The article deals with “positive” and “negative” charities, as well as ethical guidance to these activities. The text asks about the 21st century model of NGOs support for people at risk of social exclusion.